"Split" combined subsegmentectomy: A case series. Issue 3 (14th December 2021) - Hong, Ruopeng; Chen, Chun; Zheng, Wei; Zheng, Bin; Xu, Chi; Xu, Guobing
Abstract: Background: Clinically, some specific pulmonary nodules have safe resection margins that are located in multiple subsegments in the center of lung lobe. It is therefore difficult to ensure the resection margins through conventional combined subsegmentectomy or wedge resection, and thus lobectomy is required. For these types of pulmonary nodules, "split" operation was performed to fully inflate the reserved lung tissues on both sides. This study aimed to preliminarily assess the feasibility and safety of "split" operation. Methods: Cases with these types of pulmonary nodules were selected. Some of the cases were subjected to "split" operation and the operation conditions, including operation time, bleeding amount, length of hospital stay, computed tomography (CT) reexaminations, and pulmonary function, were analyzed. Results: The "split" operation was performed and successfully completed for seven patients. There was no case of conversion to thoracotomy and the median operation time, bleeding amount, and length of hospital stay were 219 min, 30.0 ml, and 4 days, respectively. No death or pulmonary complications such as pulmonary infection, lung torsion, and bronchopleural fistula occurred, and only one patient had incision fat liquefaction. After 3 months, the median percentage of preserved pulmonary function was 85.8% and a CT scan showed that the reserved lung tissues of the seven patients were well inflated and without obvious imaging findings of atelectasis. Conclusion: "Split" combined subsegmentectomy can be used as a new and safe operative method for deep pulmonary nodules with safe resection margins involving multiple subsegments in the center of the lung lobe. Abstract : "Split" combined segmentectomy can offer a novel and safe procedure for removing deep pulmonary nodules with safe resection margins involving multiple subsegments in the center of the lung lobe. In this previously unreported method, the residual lung tissues of the same lung lobe were separated just like mountains separated by a canyon.